2009
DOI: 10.1017/s0031182009991065
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards an integrated approach to molecular detection and identification ofToxoplasma gondii

Abstract: The development of simple, sensitive and rapid methods for the detection and identification of Toxoplasma gondii is important for the diagnosis and epidemiological studies of the zoonotic disease toxoplasmosis. In the past 2 decades, molecular methods based on a variety of genetic markers have been developed, each with its advantages and limitations. The application of these methods has generated invaluable information to enhance our understanding of the epidemiology, population genetics and phylogeny of T. go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
400
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 483 publications
(418 citation statements)
references
References 68 publications
(128 reference statements)
8
400
0
10
Order By: Relevance
“…This belief is changing because of greater genetic diversity as a result of sexual recombination of the parasite (Su et al 2010;Khan et al 2011). A recent study indicated that congenital T. gondii can occur in immune mothers (seropositive) when an atypical genotype overcomes the acquired resistance from the original infecting genotype (Elbez-Rubinstein et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This belief is changing because of greater genetic diversity as a result of sexual recombination of the parasite (Su et al 2010;Khan et al 2011). A recent study indicated that congenital T. gondii can occur in immune mothers (seropositive) when an atypical genotype overcomes the acquired resistance from the original infecting genotype (Elbez-Rubinstein et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Strain typing was performed using the genetic markers SAG1, 5' and 3'-SAG2, alt.SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1, Apico and CS3, as described previously (7) (12) . Reference strains, including Type I (RH), Type II (PTG) and Type III (CTG), and other strains (TgCgCa1 MAS and TgCatBr5) were used in the genotyping assays as positive controls.…”
Section: Toxoplasma Gondii Isolatesmentioning
confidence: 99%
“…Toxoplasma gondii DNA was extracted from the tissues of infected mice or cell-cultured tachyzoites and strain typing was performed using the genetic markers SAG1, 5 0 -and 3 0 -SAG2, alt.SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1 and Apico as described previously Su et al, 2010). NeighborNet phylogenetic networks were inferred using the software SplitsTree4 (Huson, 1998;Huson and Bryant, 2006;Pena et al, 2008).…”
Section: Genetic Characterisationmentioning
confidence: 99%